A PROSPECTIVE STUDY ON QUALITY OF LIFE IN PATIENTS WITH URINARY CALCULI - J, Shanmugapriya; Kumar S, Sathesh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The objective of the study is to compare the quality of life (QoL) in both men and women with urinary calculi using SF-12 questionnaire and also to improve by patient education. Patient counseling can scientifically improve the physical and mental component of certain diseases that could be a relief to the patient. Non-pharmacological approaches could be an alternative to the drug therapy. Methods: The present study involves prospective study on QoL in patients with urinary calculi. The methodology involves the collection and documentation of general information of the patient including personal history, family background, clinical findings, investigations, and medical illness associated with urinary calculi. Further, quality is documented using SF-12 questionnaire designed to assess the impact of urinary calculi and their complications. Result: It can be seen that there is an extremely significant (p<0.0001) values were obtained when compared between pre- and post-counseling phases of physical and mental component scores (PCS and MCS). Patient's PCS and MCS improved extremely significant in post-counseling. Conclusion: Patients counseling plays a major role in the management of signs and symptoms among patient with urinary calculi. Clinicians should be aware of the risk of impaired health-related QoL (HRQoL) in stone formers. A new and promising endpoint in the management of urolithiasis is improvement of HRQoL.